"Non-destructive and rapid determination of bound styrene content of styrene-butadiene rubber latex using near-infrared spectroscopy" - LI Yan, ZHONG Ming-li, ZHU Shi-yong, CUI Jia-min, ZHANG Jian-ping, CHEN Shi-long (Hecheng xiangjiao gongye)
A non-destructive and rapid determination of bound styrene content in styrene-butadiene rubber latex was studied using near-infrared spectroscopy diffuse transmission method combined with chemometrics, bound styrene content in styrene-butadiene rubber latex was determined by refractive index method, near-infrared spectral data of styrene-butadiene rubber latex were collected using Fourier transform near-infrared spectrometer, Kennard-Stone algorithm was used to divide the calibration set and validation set, partial least squares regression quantitative analysis model was established by combining the spectral preprocessing methods, such as multiple scattering correction method, second-order derivatives and Norris smoothing, etc, and the influence of screening spectral feature variables by interval partial least squares algorithm on the quantitative ana-lysis model was finally investigated. The results showed that the calibration set correlation coefficient, validation set correlation coefficient, interactive validation root mean square error and validation set root mean square error of the established model were 0.988 7, 0.818 0, 0.357 and 0.319, respec-tively. The method established by combining near-infrared spectroscopy diffuse transmission method with chemometric algorithm could realise non-destructive and rapid determination of bound styrene content in styrene-butadiene rubber latex, providing the technical support for the application of near-infrared spectroscopy analysis technology in the field of synthetic rubber intermediate quality control.